Book Review: Exploring the New Testament Vol.1 Gospels and Acts - Riste Tioma Silaen; Oren Siregar (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
New Testament is a collection of writings that provide an important historical source about the birth of Jesus, His teachings, and, how the 'Good News' spread through the Apostles after Jesus's death. Wenham and, Walton took their portion of the vast land to provide important reading for anyone who wished to study the New Testament in terms of historical, theological, narrative interpretation and, guidance in learning other things from the various writings in the New Testament. Volume 1 discusses the Four Gospels and, Acts from the historical context at the birth of Jesus, the life of the early church and, the Roman colonial era that provides its own effectiveness when interpreting the New Testament. Wenham and Walton use simple and, practical writing patterns but it is in that simplicity that becomes even more delicious when reading them. The way of speaking is used to provide beauty for readers of the Gospels and, Acts in the present so as to provide good spiritual interaction living life as a people of Christ. The Christian's hope of eternal life in Christ was also successfully explored by Wenham and Walton, as two of the most prominent writers, teachers and, pastors in the world today.